The Unfinished Story of Central European Dissent - Grim Feinberg, Joseph (Dějiny – teorie – kritika, 2014)
In this article, the author reconstructs and interprets the most significant tendencies of Central European dissident thought before 1989. The author emphasises the generally leftist orientation of dissident thought prior to 1989, while at the same time asking why after 1989 dissidents and their supporters ceased to emphasise and promote many of their erstwhile leftist ideals. He argues that the seeds of post-dissident market liberalism can be found, though often in hidden form, already in earlier dissident thought. He argues that most significant was the elision of the social as a category of dissident – and later post-dissident – thought.